Cost-effectiveness of thrombolysis vs. standard care for stroke in a public hospital in Bogotá. - Estrada-Matos, Jhonatan; Betancourt-Ayala, Andrés M.; Tocora-Rodríguez, Juan C.; Moreno-Vargas, Eder A.; Jiménez-Ortiz, Daniela; Sobrino-Mejía, Fidel (Revista Mexicana de Neurociencia)
Objective: Evaluate the cost-effectiveness of intravenous thrombolysis in the treatment of the ischemic stroke compared to standard medical management, in a public hospital in Bogotá, during the period from January to December 2024. Methods: Observational, cross-sectional study with retrospective data collection, using a sample of patients with ischemic stroke who received intravenous thrombolysis and those who did not, at Kennedy Hospital in Bogotá, Colombia. An economic evaluation was conducted to estimate the incremental cost-effectiveness ratio (ICER) of intravenous thrombolysis compared to standard medical management. Results: The number of patients who received thrombolysis was 82, while 156 patients received standard medical management. The average cost was $13,316,428.31 (3.269,77 USD) (SD $9,147,043/2.246 USD) for the thrombolysis group and $12,813,094 (3.146,17 USD) (SD $12,261,577/3.010 USD) for the non-thrombolysis group. The thrombolysis group showed a gain of 0.27 quality-adjusted life years (QALYs) with a higher cost of $503,334 (123,59 USD) compared to the standard medical management group, resulting in an ICER of $1,864,201 (457,74 USD) per QALY. The mean utility of 5.9 (SD 4.7) [95% confidence interval [CI]: 1.52-10.27; p = 0.16] for the thrombolyzed group, while for the non-thrombolyzed group, the mean was 5.35 (SD 4.6) [95% CI: 1.03-9.68; p = 0.23], the mean delta utility was 0.54 (SD 0.28) [95% CI: 0.28-0.80; p = 0.02] and the mean ICER per QALY was -1,473,833 (SD 1,656,379) [95% CI: -3,212,096 to 264,430; p = 0.81]. Conclusions: Thrombolytic therapy is associated with greater cost-effectiveness, better clinical outcomes, and reduced disability compared to standard medical management without thrombolytic therapy.